Penggunaan Metode Analisis Tugas Dalam Meningkatkan Kemampuan Melipat Kemeja Pada Anak Tunagrahita Sedang Kelas III di SLB-C Katolik Santa Anna Tomohon - Siwi, Femmy D.; Pandeinuwu, Lo-Ruhama; Dapa, Aldjon Nixon (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine whether the use of task analysis methods can improve the ability to fold shirts in moderate mentally retarded children in grade III at SLB-C Katolik Santa Anna Tomohon. The method used in this study in SSR (Single Subject Research) with an A-B-A research design consisting of baseline-1 (A1), Intervention (B), and Baseline-2 (A2). The data collection technique in this study uses the ability recording technique. The results of the study can be proven that the research subjects increased. Where in baseline-A1 before being given treatment, the percentage was 12,5%, in the intervention phase 79%, and in baseline-A2 the results were 87,5%. There was a change in the means value, which was initially baseline-A1, the value obtainted was only 0,75 until baseline-A2 reached a value of 5,25 and a change in the data level between the intervention/baseline-A1 conditions of (+3) and intervention/baseline-A2 of (+6) indicating a good trend and no overlap of data because the percentage wqas 0%. Indicating no overlapping data and the influence of intervention and target behaviour can be clearly observed. Based on the results of the study, it can be concluded that the use of the task analysis method can improve the ability to fold shirts in moderate mentally retarded children in grade III at SLB-C Katolik Santa Anna Tomohon.